AB INITIO STUDIES OF POSSIBLE FLUORINE-BEARING FOUR- AND FIVEFOLD COORDINATED AL SPECIES IN ALUMINOSILICATE GLASSES - Liu Y.; Nekvasil H. (My University, 2001)
Ab initio NMR gauge-including atomic orbital (GIAO) calculations were used to constrain assignments of resonances in 27Al NMR spectra of F-bearing alkali aluminosilicate glasses. The effect of bond angles within the range 126–150° on the chemical shift was investigated using cluster models of next-nearest atoms that are charge balanced by hydrogen atoms. GIAO calculations used geometries obtained through optimization at fixed Al-O-Si bond angles. The calculated peak positions for all of the 4-fold coordinated Al species yielded calculated 27Al NMR peak positions in good agreement with the experimental data, suggesting that any or all of the species AlF4−, AlF3O(SiH3)−, AlF2O2(SiH3)2−, and AlFO3(SiH3)3− may be present. Three of the investigated 5-fold coordinated species AlF52−, AlF3O2(SiH3)22−, and AlF2O3(SiH3)32− fit the experimental requirements well, whereas the remaining 5-fold coordinated species that were tested [AlF4O(SiH3)2−, and AlFO4(SiH3)42−] did not.